Presentation and Comparison of Unnatural Deaths Due to Different Types of Accidents in the Rajshahi District of Bangladesh - Uddin, Md Kafil; Zaman, Md Akhtar Uz; Saha, Manasi; Md Raihan, Mir (TAJ: Journal of Teachers Association, 2021)
Background: Accidental deaths are the object of public health issues. This study was designed to explore and compare the statistics of all types of accidental deaths that occurred in the Rajshahi district in 2019 and 2020. Materials and methods: The data presented here were accumulated from the forensic examination of the corresponding dead bodies, which were submitted by police from the different police stations in the Department of Forensic Medicine & Toxicology (DFMT) at RMC for postmortem examination. This study confirms and explores the number of accidental deaths based on the observation, which were analogous with corresponding signs of studied accidental events. Results: According to the data, road traffic accident (RTA) was the most prevalent cause of unnatural accidental death in both years. In 2019, the number of deaths due to unwanted bomb explosions was the lowest. But, in 2020, the lowest number of deaths were observed due to alcohol overdose. The numbers of deaths due to other accidents were almost equal. Conclusion: This study suggests taking preventive measures that may reduce accidental deaths. TAJ 2021; 34: No-1: 70-74